A new approach for psychological consultation: the psychologist at the chemist's - Molinari Enrico; Pagnini Francesco; Castelnuovo Gianluca; Lozza Edoardo; Bosio Claudio (BMC, 2012)
Abstract Background The prevalence of mental illness and psychological suffering is greater than the availability of primary care services in Europe and, in particular, in Italy. The main barriers that hinder the access to these services are economic, the lack of proximity of services and some prejudices that may promote stigma and shame. A new mental health service, named "Psychologist in the Neighbourhood" was created to intercept unexpressed needs for psychological assistance. The service allows everyone to ask for free psychological consultation, consisting of no more than four meetings with a psychologist, in certain chemists' shops around the city of Milan. This article aims to present the service specific features of this initiative and the results of a pilot study. Methods Information gathered on all users included socio-demographic data, the reasons why they approached this specific service, how they learnt about it, the main presented problem and, for a random sub-group, the level of psychological well-being (as measured by the PGWBI). Socio-demographic data were compared with previously collected information about general users of psychological services. The outcome of the intervention was assessed by the clinicians. Results During the two-year project a total of 1,775 people accessed the service. Compared to traditional users of psychological services, the participants in this service were characterized by a higher presence of females, unemployed and retired people. The main factors encouraging access were proximity and the fact that the service was free of charge. Many of the users were redirected to more specific services, while for about a third of the sample the consultation cycle was sufficient to resolve the presented problem. Conclusions The interest and participation of the population was high and this initiative intercepted an unexpressed requirement for psychological support. Free access and home proximity, were the main reasons for accessing this specific service. Subjects were mostly re-directed to appropriate services, while about a third of the sample addressed and resolved their problem with the psychologist in the chemist's shop. These encouraging results suggest the benefits of bringing psychological consultations closer to citizens, particularly to those who cannot afford it, reducing socio-economic inequalities.